Seismic Response Validation of Simulated Soil Models to Vertical Array Record During A Strong Earthquake - Rena Misliniyati; Lindung Zalbuin Mase; Masyhur Irsyam; Hendriawan Hendriawan; Andika Sahadewa (Journal of Engineering and Technological Sciences, 2019)
Several soil models, such as linear elastic, equivalent linear, and non-linear models, are employed in seismic ground response analysis. The aim of this study was to validate the seismic responses at ground surface of several soil models with the vertical array record of the Kobe earthquake. One-dimensional seismic response analyses were performed at Port Island using several soil models. The responses at ground surface from the simulated soil models were validated with the vertical array record of the Kobe earthquake. The results showed that the extended hyperbolic model yielded the most appropriate response according to the Kobe earthquake's recorded motion. This means that this model can be considered a suitable soil model to predict the response of strong earthquakes. In general, the results support the recommendation to select the most appropriate soil model for seismic ground response analysis.